PREPARATION AND IMPLEMENTATION OF MARKETING PLAN : PODCAST PROGRAM AT SUBANG HOSPITAL - Gugyh Susandy; Mutqi Sopiawandi; Gandhes Dwi Puspaningtyas; Wiwin Widiawati (Gapura (Garba Pembangunan Masyarakat), 2023)
It is hope that the subang regional general hospital will be able to further increase the activeness of the existing hospital’s social media by routinely dessimenating information on hospital program activities and disseminating health information to the public. It is hoped that the hospital can improve its markeing management trough podcast media and maximize podcast media management so that it can attractpublic attention and can also increase the number of home social media followers. This research is only an illustration of the uss of podcast media published on instagram, therefore it is recommended for further research to carry our further research regarding the impact of podcast media on hospital performance. It is recommended that the ministry of health conduct training on managing the us of social media. Subang Hospital must further increase promotional/marketing activities regarding safe and comfortable inpatient services as long as patient/families implement health protocols, both in the internal and external environment of the hospital by utilizing electronic media owned by the RSUD (Instagram, Whatsapp Group, Facebook, Website) radio media, and other electronic media as well as through binders, leaflets, pamphlets, and banners, brochures, print media and other media).